Tensile bond strengths of hard chairside reline resins as influenced by water storage - Cucci, A. L M [UNESP]; Racked, R. N. [UNESP]; Giampaolo, E. T. [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley, 1999)
Due to gradual resorption of the edentulous ridge bone, removable prostheses often require denture base relines to improve fit and stability. This research evaluated the bond strength between one heat-cured acrylic resin (Lucitone 550®) and two hard chairside reline resins, after two different periods of storage in water (50 h and 30 days). The bond strength was evaluated using a tensile test. The mode of failure, adhesive or cohesive, was also recorded. The results submitted to the Kruskal-Wallis test indicated that the highest tensile strengths were achieved with intact Lucitone 550® denture base resin in both periods of storage in water. After 50 h of storage in water, Duraliner II® reline material exhibited the highest bond strength to the denture base resin. After 30 days of storage in water, Duraliner II® reline resin demonstrated a significant reduction in adhesion, showing lower tensile bond strength than Kooliner® material. Both hard chairside reline materials failed adhesively across Lucitone 550® denture base resin, in both periods of time. © 1999 Blackwell Science Ltd.
Keywords: acrylic acid resin; duraliner II; kooliner; Lucitone; water; adhesion; chemistry; dental bonding; denture; human; materials testing; surface property; tensile strength; time; Acrylic Resins; Adhesiveness; Dental Bonding; Denture Bases; Denture Liners; Denture Rebasing; Denture Retention; Humans; Materials Testing; Surface Properties; Tensile Strength; Time Factors; Water